2016
DOI: 10.1089/jwh.2015.5475
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluation of Faculty Physicians: Gender Differences in Teaching Evaluations

Abstract: Porter, Annie C.; Lypson, Monica L.; Santen, Sally A.; Christner, Jennifer G.; Grum, Cyrl M.; and Hammoud, Maya M., ,"Student evaluation of faculty physicians: gender differences in teaching evaluations." Journal of Women's Health. 25,5. 453-456. (2016 Purpose: To investigate whether there is a difference in medical student teaching evaluations for male and female clinical physician faculty. Methods:The authors examined all teaching evaluations completed by clinical students at one North American medical schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…They receive quantitative and qualitative evaluations that are worse than their male counterparts from both nurses and faculty . Similarly, female faculty receive poorer teaching evaluations from students in comparison to their male counterparts . Female faculty and residents report higher rates of sexual harassment, gender bias, and discrimination directed from both patients and colleagues and ultimately higher rates of burnout and attrition from the workforce .…”
mentioning
confidence: 99%
“…They receive quantitative and qualitative evaluations that are worse than their male counterparts from both nurses and faculty . Similarly, female faculty receive poorer teaching evaluations from students in comparison to their male counterparts . Female faculty and residents report higher rates of sexual harassment, gender bias, and discrimination directed from both patients and colleagues and ultimately higher rates of burnout and attrition from the workforce .…”
mentioning
confidence: 99%
“…A recent study that investigated for differences in medical student evaluations of male and female faculty physicians on 4 required clinical rotations (obstetrics and gynecology, pediatrics, surgery, and internal medicine) found female faculty physicians received lower scores on the evaluation item ''overall quality of teaching'' in all 4 rotations. 8 No differences were found in faculty evaluations based on medical student gender. 8 The findings suggest the transient relationships between medical students and faculty physicians may be subject to unconscious gender bias.…”
Section: Introductionmentioning
confidence: 94%
“…8 No differences were found in faculty evaluations based on medical student gender. 8 The findings suggest the transient relationships between medical students and faculty physicians may be subject to unconscious gender bias. These findings are in contrast to a large study of resident evaluations of faculty, which showed no overall gender difference in mean ratings, 9 although there was a significant interaction effect with female faculty rated highest by female residents, and male faculty rated highest by male residents.…”
Section: Introductionmentioning
confidence: 94%
“…SETs were found to be significantly biased against female faculty members in several studies. [27][28][29][30][31][32][33][34] While gender inequalities in SETs have been described since the mid-1970s, surprisingly little has changed with regards to gender bias. 30 Nevertheless, SETs continue to be used today as objective measures of teaching performance and to determine faculty promotion and tenure.…”
Section: Sets Are Biased Against Female Facultymentioning
confidence: 99%
“…In one study of academic physicians, female faculty members received significantly lower SET scores than male faculty members in all core clinical rotations. 33 Another study found a gender bias against females in multi-instructor courses that were co-taught by faculty groups that were gender-and ethnically diverse. 34 SETs also provide a venue for students to anonymously express their gender biases in more obvious ways.…”
mentioning
confidence: 99%